Evaluating the fruit production and quality of cherry tomato (solanum lycopersicum var. cerasiforme) / evaluación de la producción y calidad del fruto del tomate cereza solanum lycopersicum var. cerasiforme (2012)
The greatest genetic diversity of tomato (Solanum lycopersicum L.) in terms of fruit quality characteristics such as flavor, aroma, color, and lycopene and β-carotene contents is found in wild species. This study evaluated the agronomic characteristics and fruit quality of 30 cherry tomato introductions of the germplasm bank of the Universidad Nacional de Colombia - Sede Palmira in trials conducted at the Montelindo experimental farm of the Universidad de Caldas (1010 m above sea level, average temperature 22.8 °C, average annual rainfall 2200 mm, 76% relative humidity). A 5 x 6 rectangular lattice experimental design was used with 30 treatments (introductions) and a commercial control (Sweet Million), 4 replicates/treatment, and 5 plants/replicate as experimental unit. The descriptors used were those suggested by the former International Plant Genetic Resources Institute, now Bioversity International. Data were statistically analyzed by ANOVA and Duncan’s means test using the SAS program. In addition, principal component and cluster dendrogram analyses using the SAS Princom and Cluster procedure (SAS Institute, Cary, NC) were performed. Six principal components accounted for 80.39% of the morphological variability of the introductions evaluated. The most promising materials in terms of average fruit weight, yield per plant and per hectare, and soluble solids, vitamin C and lycopene contents were IAC1624, IAC391, IAC3652, LA2131, IAC424, IAC1621, IAC426, LA1480 and IAC1688. The broad phenotypic variability observed in the evaluated introductions favors the potential selection and breeding of tomato for traits associated with fruit production and quality. / La mayor diversidad genética del tomate (Solanum lycopersicum L.) en términos de características de calidad del fruto como sabor, aroma, coloración y contenidos de licopeno y β-caroteno se encuentra en especies silvestres. Este estudio evaluó las características agronómicas y de calidad del fruto de 30 introducciones de tomate cereza provenientes del banco de germoplasma de la Universidad Nacional de Colombia –Sede Palmira en ensayos realizados en la granja Montelindo de la Universidad de Caldas (1010 m sobre el nivel del mar; temperatura media, 22,8°C; precipitación promedio anual, 2200 mm; humedad relativa, 76%). Se usó un diseño experimental de látice rectangular 5 x 6, con 30 tratamientos (introducciones) y un testigo comercial (Sweet Million), 4 repeticiones/tratamiento y 5 plantas/repetición como unidad experimental. Se utilizaron descriptores sugeridos por el antiguo Instituto Internacional de Recursos Fitogenéticos, ahora Bioversity International. Los datos fueron analizados estadísticamente utilizando análisis de varianza y la prueba de promedios de Duncan a través del programa SAS. Adicionalmente se realizaron análisis de componentes principales y agrupamiento por dendrograma por medio del procedimiento Princom y Cluster de SAS (SAS Institute, Cary, NC). Seis componentes principales explicaron el 80,39% de la variabilidad morfológica de las introducciones evaluadas. Los materiales más promisorios en términos de peso promedio de fruto, producción por planta, rendimiento y contenidos de sólidos solubles, vitamina C y licopeno fueron IAC1624, IAC391, IAC3652, LA2131, IAC424, IAC1621, IAC426, LA1480 y IAC1688. La amplia variabilidad fenotípica de las introducciones evaluadas favorece la posibilidad de selección y mejoramiento genético en tomate por caracteres asociados a la producción y calidad del fruto.